ISLAM DAN BUDAYA KONSUMTIF: KOMODIFIKASI SIMBOL KEAGAMAAN DALAM MASYARAKAT MUSLIM URBAN - Atiqahwati, Arih Inas (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2025)
The phenomenon of the commodification of religious symbols in urban Muslim societies, particularly in major Indonesian cities such as Jakarta and Bandung, has become more prominent with the growing consumerist culture. Religious symbols, once used as a means to express spiritual beliefs, have now transformed into commodities that function as tools to display social identity and individual status. This study aims to analyze the impact of the commodification of religious symbols in shaping urban society's religious perceptions, with an emphasis on the role of social media and the increasingly popular halal-labeled products among consumers. The research uses a qualitative method with a phenomenological approach. Data were analyzed through in-depth interviews with a diverse range of informants, including social media users, halal business owners, and religious figures. The interviews were transcribed and analyzed thematically to identify key themes. Focus group discussions and participatory observations at community events and halal product markets were conducted to explore collective perspectives on religious symbols in consumption. The results indicate that religious symbols have shifted from their spiritual function to become symbols of social status, which in turn diminishes the spiritual value they once held. This process of commodification is further accelerated by the role of social media, which turns religious preaching into an attractive consumer lifestyle, with social media users often showcasing religious symbols as part of their identity. The study finds that the consumption of religious symbols is more focused on seeking social prestige rather than expressing faith. Therefore, it is important to critique this phenomenon and preserve the authenticity of religious symbols to prevent them from becoming market commodities that lose their meaning, in order to maintain spiritual and social integrity amid modern capitalism.